Emily S.K. Anderson. Seals, craft and community in Bronze Age Crete. - Younger, John G. (Journal of Greek Archaeology, 2019)
After a list of illustrations (191 b/w), acknowledgements, and an introduction, five chapters and a lengthy appendix constitute the core of the book. There then follow references (bibliography), (end)notes, and an index. The book’s introduction and five chapters mostly present anthropological theories and constructions of Cretan society in the late PrePalatial period (ca. 2300–1900 BCE) seen through the lenses of other, presumably similar societies, cultures, and ethnologies as studied by a variety of quoted scholars. The chapter titles give an indication of themes, sometimes promising archaeological data (e.g., ‘Identity and Relation through Early Cretan Glyptic’ [ch. 2], ‘In the Hands of the Craftsperson: Innovation and Repetition across Cretan Communities’ [ch. 4]), sometimes teasing the reader with poetic playfulness (e.g., ‘Rethinking Prepalatial Crete: Social Innovation on an Island of Persistence’ [ch. 1], ‘Distance and Nearness: Fundamental Changes to the Dynamics of Seal Use in Late Prepalatial Crete’ [ch. 3]).